Acoustic radiation force impulse (ARFI) and high-frequency ultrasound of the liver surface for the diagnosis of compensated liver cirrhosis - Pfeifer, Lukas; Görtz, Rüdiger; Sturm, Jörg; Wachter, David; Riener, M. O.; Schwitulla, Judith; Bernatik, T.; Neurath, Markus; Strobel, Deike (Ultraschall in der Medizin, 2014)
To evaluate the diagnostic value of acoustic radiation force impulse (ARFI) and high-frequency ultrasound of the liver surface, using histology as a gold standard for the diagnosis of compensated liver cirrhosis.73 patients without ascites undergoing liver biopsy were included in the study. The left and right liver lobes were examined with ARFI and high-frequency ultrasound. Liver surface irregularity was quantified using image analysis software to calculate the difference between the real surface and the approximated physiological surface through a 20 mm standardized line.There is a significant difference between cirrhotic and non-cirrhotic patients for both quantified liver surface (QLS) and ARFI (p < 0.001). The mean values for QLS of the left lobe were 0.71 ± 0.24 mm and 1.17 ± 0.80 mm, of the right lobe 0.56 ± 0.26 mm and 0.87 ± 0.26 mm for non-cirrhotic and cirrhotic patients, respectively. The mean values of ARFI measurements of the left lobe were 2.04 ± 0.76 m/s and 2.85 ± 0.81 m/s, of the right lobe 1.65 ± 0.61 m/s and 3.02 ± 0.77 m/s for non-cirrhotic and cirrhotic patients, respectively. Diagnostic accuracy (AUROC) was 0.78/0.80 for QLS and 0.77/0.91 for ARFI of the left/right lobe, respectively. ARFI of the right lobe is significantly better than ARFI of the left (p = 0.023) or QLS of the left (p = 0.025)/right (p = 0.046) lobe of the liver.Assessment of liver surface irregularity by high-frequency ultrasound (QLS) is a useful diagnostic test for the assessment of compensated liver cirrhosis. ARFI of the right liver lobe is significantly better than high-frequency ultrasound (QLS of the left/right lobe of the liver) and ARFI of the left lobe of the liver.
EVALuna2:1858

Acoustic Radiation Force Impulse (ARFI) Elastography in Autoimmune and Cholestatic Liver Diseases - Görtz, Rüdiger; Gassmann, Luise; Strobel, Deike; Wildner, Dane; Schellhaas, Barbara; Neurath, Markus; Pfeifer, Lukas (Annals of Hepatology, 2019)
Introduction. Acoustic Radiation Force Impulse (ARFI) elastography evaluates hepatic fibrosis non-invasively and has been mainly validated in viral hepatitis. Data on rare liver diseases such as autoimmune hepatitis (AIH), overlap syndrome, primary biliary cholangitis (PBC) or primary sclerosing cholangitis (PSC) are sparse. Material and methods. 85 patients (including 31 AIH, 26 PBC, 16 PSC and 3 PSC- and 9 PBC-AIH-overlap syndromes) were retrospectively analysed pointing at ARFI elastography of the liver and the correlation with histologic Ishak fibrosis score (F0-6). Results of shear wave velocities (m/s) were expressed as mean +/- standard deviation. Results. The mean shear wave velocity of all 85 patients showed 1.80 +/- 0.84 m/s (0.74-3.98). The ARFI elastography values correlated with the degree of fibrosis in all patients overall and in patients with AIH, overlap syndrome and PSC, respectively. The subgroup of 26 patients with PBC (only with Ishak F <= 3) revealed no correlation between ARFI and these early fibrosis stages (r = 0.019, p = 0.927). ARFI elastography correlated with bilirubin, AST, but not with patient age, body mass index or measurement depth. The cut-off of 2.04 m/s for detecting cirrhosis (Ishak F >= 5) leads to a sensitivity of 90.0% and specificity of 74.7% (AUROC 87.2%). Conclusion. ARFI elastography can evaluate fibrosis in AIH, PSC and PSC-/PBC-AIH-overlap syndrome with good accuracy for the detection of hepatic cirrhosis. Shear wave velocities in PBC should be interpreted with caution in early stages of fibrosis.
CRIS-Team WoS Importer:2019-03-20

Acoustic radiation force impulse (ARFI) shear wave elastography of the bowel wall in healthy volunteers and in ulcerative colitis - Görtz, Rüdiger; Lueke, Christian; Schellhaas, Barbara; Pfeifer, Lukas; Wildner, Dane; Neurath, Markus; Strobel, Deike (Acta Radiologica Open, 2019)
Background Acoustic radiation force impulse (ARFI) elastography is a non-invasive, ultrasound-based approach of evaluation of tissue elasticity. It has not yet been systematically applied to the bowel wall. Purpose To perform ARFI elastography of the bowel wall in healthy volunteers and patients with ulcerative colitis (UC). Material and Methods A high-frequency ultrasound (with bowel wall thickness and vascularization score) and an ARFI elastography of the bowel wall were performed in 20 patients with UC and 13 healthy volunteers. At least 10 ARFI measurements were obtained within the terminal ileum and the ascending, transverse, descending, and sigmoid colon and correlated with results of high-frequency ultrasound. Results The UC group had mostly moderate disease activity. All patients had signs of inflammation upon B-mode ultrasound. Eight patients showed an ulcerative (ileo)pancolitis. Overall, ARFI elastography values and wall thickness were higher in the UC group than in the group of healthy volunteers (P = 0.021 and P < 0.001, respectively). ARFI velocities of the separate segments were significantly higher in the transverse (P = 0.045) and sigmoid colon (P = 0.032) in case of UC. Conclusion ARFI elastography of the bowel wall of the colonic frame and the terminal ileum is feasible but shows high standard deviation. ARFI shear wave velocities appear to be slightly higher in patients with UC than in healthy volunteers, particularly in the sigmoid and transverse colon. Further studies are needed.
CRIS-Team WoS Importer:2019-04-30

Acoustic radiation force impulse elastography: comparison and combination with other noninvasive tests for the diagnosis of compensated liver cirrhosis - Pfeifer, Lukas; Adler, Werner; Zopf, Steffen; Wildner, Dane; Görtz, Rüdiger; Schellhaas, Barbara; Neurath, Markus; Strobel, Deike; Siebler, Jürgen (European Journal of Gastroenterology & Hepatology, 2017)
BACKGROUND AND AIMS: The aim of this study was to compare acoustic radiation force impulse (ARFI) elastography with other noninvasive tests and to develop a new score for the assessment of liver fibrosis/cirrhosis. MATERIALS AND METHODS: B-mode ultrasound (including high-frequency liver surface evaluation), routine blood tests, ARFI quantification, and mini-laparoscopic liver evaluation were obtained in compensated patients scheduled for mini-laparoscopic biopsy. Our new cirrhosis score (CS) for the assessment of liver cirrhosis, based on a linear combination of ARFI, platelet (PLT), liver surface, and prothrombin index (PI), was calculated by linear discriminant analysis. Its performance was compared with ARFI-elastography, APRI, FIB-4, alanine aminotransferase (ALT)/aspartate aminotransferase (AST)-ratio, PLT, and PI. For the diagnosis of cirrhosis, a combined gold standard (cirrhosis at histology and/or at macroscopic liver evaluation) was used. RESULTS: In total, 171 patients, of whom 38 had compensated cirrhosis, were included. The CS was significantly better for the diagnosis of cirrhosis compared with ARFI (P=0.028), APRI (P=0.012), PLTs (P=0.013), PI (P=0.025), and ALT/AST ratio (P=0.001), but not the FIB-4 score (P=0.207), with an area under the receiver operating characteristic curve of 0.92 [95% confidence interval (CI): 0.87-0.97], 0.86 (95% CI:0.79-0.93), 0.80 (95% CI: 0.72-0.87), 0.79 (95% CI: 0.7-0.87), 0.81 (95% CI: 0.73-0.89), 0.72 (95% CI:0.64-0.81), and 0.86 (95% CI: 0.8-0.93), respectively. Sensitivity, specificity, positive predictive value, and negative predictive value for CS were 87%, 86%, 63%, and 96%, respectively. The FIB-4 score was significantly superior to the APRI score (P=0.041) and the ALT/AST ratio (P=0.011), with no significant difference from ARFI elastography (P=0.88) for the diagnosis of cirrhosis. CONCLUSION: Combining ARFI elastography with other noninvasive tests that are used routinely in the workup of patients with suspected liver disease can improve diagnostic accuracy for compensated liver cirrhosis as compared with ARFI elastography alone. The FIB-4 score showed an overall comparable diagnostic accuracy to ARFI-elastography for compensated cirrhosis.
EVALuna2:33816

Acoustic radiation force impulse shear wave elastography (ARFI) of acute and chronic pancreatitis and pancreatic tumor - Görtz, Rüdiger; Schuderer, Johanna; Strobel, Deike; Pfeifer, Lukas; Neurath, Markus; Wildner, Dane (European Journal of Radiology, 2016)
Acoustic Radiation Force Impulse (ARFI) elastography evaluates tissue stiffness non-invasively and has rarely been applied to pancreas examinations so far. In a prospective and retrospective analysis, ARFI shear wave velocities of healthy parenchyma, pancreatic lipomatosis, acute and chronic pancreatitis, adenocarcinoma and neuroendocrine tumor (NET) of the pancreas were evaluated and compared.In 95 patients ARFI elastography of the pancreatic head, and also of the tail for a specific group, was analysed retrospectively. Additionally, prospectively in 100 patients ARFI was performed in the head and tail of the pancreas.A total of 195 patients were included in the study. Healthy parenchyma (n=21) and lipomatosis (n=30) showed similar shear wave velocities of about 1.3m/s. Acute pancreatitis (n=35), chronic pancreatitis (n=53) and adenocarcinoma (n=52) showed consecutively increasing ARFI values, respectively. NET (n=4) revealed the highest shear wave velocities amounting to 3.62m/s. ARFI elastography showed relevant differences between acute pancreatitis and chronic pancreatitis or adenocarcinoma. With a cut-off value of 1.74m/s for the diagnosis of a malignant disease the sensitivity was 91.1% whereas the specificity amounted to 60.4%.ARFI shear wave velocities present differences in various pathologies of the pancreas. Acute and chronic pancreatitis as well as neoplastic lesions show high ARFI values. Very high elasticity values may indicate malignant disease of the pancreas. However, there is a considerable overlap between the entities.
EVALuna2:2188

Comparison of Acoustic Radiation Force Impulse (ARFI) Elastography Measurements with the 4C1 Transducer to the 6C1HD Transducer: A Phantom and Patient Study - Pfeifer, Lukas; Görtz, Rüdiger; Neurath, Markus; Strobel, Deike; Wildner, Dane (Ultraschall in der Medizin, 2016)
Purpose: The aim of this study was to evaluate whether acoustic radiation force impulse (ARFI) elastography done with the 4C1 probe yields comparable results to the recently introduced 6C1HD probe. Materials and Methods: Measurements with the 4C1 and 6C1HD probes (Acuson S2000) were performed and compared in four different inclusions of an elasticity phantom model (QA049 CIRS) as well as in the liver of healthy individuals and patients with liver cirrhosis. Results: Measurements with the 6C1HD probe were slightly higher in all phantom inclusions (8, 14, 45, 80kPA) with a mean of 1.48 m/s (95 %-CI; 1.47 - 1.49), 2.18 m/s (95 %-CI; 2.17 - 2.19), 3.61 m/s (95 %-CI; 3.57 - 3.64) and 4.34 m/s (95 %-CI; 4.29 - 4.39) compared to the 4C1 transducer with 1.46 m/s (95 %-CI; 1.45 - 1.47), 2.15 m/s (95 %-CI; 2.14 - 2.16), 3.39 m/s (95 %-CI; 3.37 - 3.41) and 3.98 m/s (95 %-CI; 3.75 - 4.21), respectively (p = 0.04, p < 0.01, p < 0.01, p < 0.01). Cirrhotic patients (n = 40) had a higher mean shear wave speed with 3.00 m/s (95 %-CI; 2.80 - 3.21) with the 6C1HD transducer compared to 2.81 m/s (95 %-CI; 2.64 - 2.99) with the 4C1 transducer (p = 0.03). Healthy individuals (n = 20) had a mean shear wave speed of 1.12 m/s (95 %-CI; 1.06 - 1.17) with the 6C1HD probe and 1.12 m/s (95 %-CI; 1.05 - 1.19) with the 4C1 probe (p = 0.96). Conclusion: ARFI values assessed with a 6C1HD transducer are slightly higher than measurements with a 4C1 transducer in an ARFI phantom and in patients with liver cirrhosis. As the difference is small, current cut-off values keep their usefulness but should be interpreted with caution if measurements are close to the cut-off.
EVALuna2:2195

Computer-aided detection of colorectal polyps using a newly generated deep convolutional neural network: from development to first clinical experience - Pfeifer, Lukas; Neufert, Clemens; Leppkes, Moritz; Waldner, Maximilian; Hafner, Michael; Beyer, Albert; Hoffman, Arthur; Siersema, Peter D.; Neurath, Markus; Rath, Timo (European Journal of Gastroenterology & Hepatology, 2021)
Aim The use of artificial intelligence represents an objective approach to increase endoscopist's adenoma detection rate (ADR) and limit interoperator variability. In this study, we evaluated a newly developed deep convolutional neural network (DCNN) for automated detection of colorectal polyps ex vivo as well as in a first in-human trial.
CRIS-Team WoS Importer:2022-03-18

Diagnostic accuracy and interobserver variability of Dynamic Vascular Pattern (DVP) in primary liver malignancies - A simple semiquantitative tool for the analysis of contrast enhancement patterns - Schellhaas, B.; Waldner, Maximilian; Goertza, R. S.; Vitali, Francesco; Kielisch, Ch.; Pfeifer, Lukas; Strobel, Deike; Janka, Rolf Matthias; Neurath, Markus; Wildner, Dane (Clinical Hemorheology and Microcirculation, 2017)
Contrast-enhanced ultrasound (CEUS) is a valuable tool in the diagnostic approach of focal liver lesions, but occasionally subjective and observer-dependent. Semiquantitative evaluation of dynamic CEUS (DCEUS) with standardised software programmes such as Dynamic Vascular Pattern (DVP) could help to improve diagnostic accuracy and objectivity in liver tumour assessment.The present study aimed at evaluation of diagnostic accuracy of DVP in a clinical setting.DVP images of 52 focal liver lesions [30 hepatocellular carcinomas (HCCs), 15 intrahepatic cholangiocellular carcinomas (ICCs), 7 focal nodular hyperplasias (FNHs)] were analysed by four blinded observers with different levels of CEUS-experience. Diagnostic accuracies for the assessment of dignity and entity were evaluated.Mean sensitivity, specificity, positive and negative predictive value for detection of malignancy with DVP were 48.4% /67.8% /92.7% and 29.3%, respectively. Total diagnostic accuracies for dignity/entity were 63.9% /38.5% (HCC: 58.3% /25.8%; ICC: 73.3% /50%; FNH: 67.9% /67.9%). Interreader-agreement was moderate (?= 0.42-0.58). Differential diagnosis between ICC and HCC was most challenging.Although developed to improve diagnostic accuracy and objectivity in the assessment of focal liver lesions, DVP alone seems insufficient for differential diagnosis of HCC, ICC and FNH and cannot replace the skills of an experienced observer.
EVALuna2:14711

Diagnostic accuracy of contrast-enhanced ultrasound for the differential diagnosis of hepatocellular carcinoma: ESCULAP versus CEUS-LI-RADS - Schellhaas, Barbara; Görtz, Rüdiger; Pfeifer, Lukas; Kielisch, Christian; Neurath, Markus; Strobel, Deike (European Journal of Gastroenterology & Hepatology, 2017)
OBJECTIVE: A comparison is made of two contrast-enhanced ultrasound (CEUS) algorithms for the diagnosis of hepatocellular carcinoma (HCC) in high-risk patients: Erlanger Synopsis of Contrast-enhanced Ultrasound for Liver lesion Assessment in Patients at Risk (ESCULAP) and American College of Radiology Contrast-Enhanced Ultrasound-Liver Imaging Reporting and Data System (ACR-CEUS-LI-RADSv.2016). PATIENTS AND METHODS: Focal liver lesions in 100 high-risk patients were assessed using both CEUS algorithms (ESCULAP and CEUS-LI-RADSv.2016) for a direct comparison. Lesions were categorized according to size and contrast enhancement in the arterial, portal venous and late phases.For the definite diagnosis of HCC, categories ESCULAP-4, ESCULAP-Tr and ESCULAP-V and CEUS-LI-RADS-LR-5, LR-Tr and LR-5-V were compared. In addition, CEUS-LI-RADS-category LR-M (definitely/probably malignant, but not specific for HCC) and ESCULAP-category C [intrahepatic cholangiocellular carcinoma (ICC)] were compared.Histology, CE-computed tomography and CE-MRI served as reference standards. RESULTS: The reference standard among 100 lesions included 87 HCCs, six ICCs and seven non-HCC-non-ICC-lesions. For the diagnosis of HCC, the diagnostic accuracy of CEUS was significantly higher with ESCULAP versus CEUS-LI-RADS (94.3%/72.4%; p<0.01). Sensitivity, specificity and positive predictive value (PPV) and negative predictive value for ESCULAP/CEUS-LI-RADS were 94.3%/72.4%; 61.5%/69.2%; 94.3%/94%; and 61.5%/27.3%, respectively.The diagnostic accuracy for ICC (LR-M/ESCULAP-C) was identical with both algorithms (50%), with higher PPV for ESCULAP-C versus LR-M (75 vs. 50%). CONCLUSION: CEUS-based algorithms contribute toward standardized assessment and reporting of HCC-suspect lesions in high-risk patients. ESCULAP shows significantly higher diagnostic accuracy, sensitivity and negative predictive value with no loss of specificity compared with CEUS-LI-RADS. Both algorithms have an excellent PPV. Arterial hyperenhancement is the key feature for the diagnosis of HCC with CEUS. Washout should not be a necessary prerequisite for the diagnosis of definite HCC. CEUS-LI-RADS in its current version is inferior to ESCULAP for the noninvasive diagnosis of HCC. There are two ways to improve CEUS-LI-RADS: firstly, combination of the categories LR-4 and LR-5 for the diagnosis of definite HCC, and secondly, use of subtotal infiltration of a liver lobe as an additional feature.
EVALuna2:33804

Differentiation of malignant liver tumors by software-based perfusion quantification with dynamic contrast-enhanced ultrasound (DCEUS) - Wildner, Dane; Schellhaas, Barbara; Strack, Daniel; Görtz, Rüdiger; Pfeifer, Lukas; Fießler, Cornelia; Neurath, Markus; Strobel, Deike (Clinical Hemorheology and Microcirculation, 2019)
BACKGROUND: Enhancement patterns on contrast-enhanced ultrasound (CEUS) help to distinguish different liver tumors.
CRIS-Team WoS Importer:2019-04-16

Dynamic Contrast-Enhanced Ultrasound (DCE-US) for the Characterization of Hepatocellular Carcinoma and Cholangiocellular Carcinoma - Wildner, D.; Pfeifer, Lukas; Görtz, Rüdiger; Bernatik, T.; Sturm, J.; Neurath, Markus; Strobel, Deike (Ultraschall in der Medizin, 2014)
Purpose: In a prospective study, we compared the different perfusion kinetics of HCC and ICC using dynamic contrast-enhanced ultrasound (DCE-US). Materials and Methods: Patients with proven HCC and ICC were included. Three-minute video clips of CEUS examinations (CPS - low MI mode) after a bolus injection of 1.2 ml SonoVue(®) were recorded and analyzed with quantification software (VueBox(®)). Parameters for the arterial contrast enhancement [rise time (RT), time-to-peak (TTP)] towards portal venous contrast enhancement [mean transit time (local) (mTTl) and fall time (FT)] were quantified. Furthermore, contrast wash-out after peak enhancement (PE) (40 s, 80 s, 100 s and 120 s after PE) was compared between HCC and ICC. Results: 43 patients with proven HCC (n = 23 HCC; cirrhosis n = 16) and ICC (n = 20 ICC; Cirrhosis n = 6) were examined. No statistical difference of the arterial DCEUS parameters was found between HCC and ICC. Contrast enhancement of the portal venous and late phases showed significantly lower values in the ICC group indicating early wash-out of the contrast agent: mTTl (p = 0.0209): HCC 118.4 s (SD± 88.4); ICC 64.8 s (SD± 49.7). FT (p = 0.0433): HCC 42.5 s (SD± 27.7); ICC 27.7 s (SD± 16.2). The percental loss of intensity at a definite time point after PE was significantly higher in ICC than in HCC lesions. Conclusion: DCE-US is able to detect and quantify differences in perfusion kinetics between HCC and ICC. Whereas arterial contrast enhancement patterns may overlap between HCC and ICC, a timed characterization of wash-out kinetics may offer an additional tool to characterize HCC and ICC. The presence of a rapid loss of signal intensity in the early portal venous phase is significantly higher in ICC than in HCC lesions.
EVALuna2:1876

Dynamics of Fukuoka Criteria and Patient Management in Pancreatic Intraductal Papillary Mucinous Neoplasms (IPMNs) During Follow-Up - Schellhaas, Barbara; Vitali, Francesco; Wildner, Dane; Görtz, Rüdiger; Pfeifer, Lukas; Konturek, Peter C.; Neurath, Markus; Strobel, Deike (Medical Science Monitor, 2017)
BACKGROUND Pancreatic intraductal papillary mucinous neoplasms (IPMNs) present a clinical challenge. Evidence-based guidelines are lacking. The so-called "Fukuoka criteria" were developed to assess the risk of malignancy in IPMNs upon imaging. However, little is known about their diagnostic value and the natural course of IPMNs. Thus, the aim of this study was the assessment of Fukuoka criteria and patient management in pancreatic IPMNs -during follow-up. MATERIAL AND METHODS IPMNs were identified via retrospective survey of endoscopic ultrasound (EUS) examinations. Fukuoka criteria were assessed on EUS findings and additional imaging (CT, MRI, ultrasound). Patients' symptoms and comorbidities were recorded. Dynamics of Fukuoka criteria and patient management were compared at first presentation and during follow-up. RESULTS We screened 1324 EUS examinations. Sixty-five patients (male/female, 14/37; mean age, 68.8 years; range, 48-85 years) with IPMNs were identified (57 branch duct (BD-)IPMNs, 3 main duct (MD-) IPMNs, 5 mixed-type (MT)-IPMNs). Seven patients received surgical resection (4 BD-IPMNs, 2 MD-IPMNs, 1 MT-IPMN). Nine BD-IPMNs had neither surgery nor follow-up. Fifty-one patients (44 BD-IPMNs, 2 MD-IPMNs, 5 MT-IPMNs) underwent follow-up (mean duration, 18.7 months; range, 3-139 months). There were 15/51 patients who were initially Fukuoka-positive. One MD-IPMN, 4/5 MT-IPMNs, and 13/44 BD-IPMNs showed progressive changes but were not resected due to patients' refusal or comorbidities. Four BD-IPMNs converted to Fukuoka-positive. CONCLUSIONS Evidence-based guidelines for non-invasive dignity assessment of IPMNs are lacking. In our study, MD-IPMNs displayed greater dynamics than BD-IPMNs and MT-IPMNs concerning Fukuoka criteria. Prospective long-term studies are needed to clarify prognostic significance of the single Fukuoka criteria and sensible duration of follow-up.
EVALuna2:33822

Effects of liver cirrhosis and patient condition on clinical outcomes in intrahepatic cholangiocarcinoma: a retrospective analysis of 156 cases in a single center - Jesper, Daniel; Heyn, Sabrina; Schellhaas, Barbara; Pfeifer, Lukas; Görtz, Rüdiger; Zopf, Steffen; Neurath, Markus; Strobel, Deike (European Journal of Gastroenterology & Hepatology, 2018)
OBJECTIVE: The incidence of intrahepatic cholangiocarcinoma (iCCA) has been increasing over the past few decades. Liver cirrhosis is an independent risk factor for the development of iCCA. This study aimed to examine the prognostic impact of liver cirrhosis and patient condition on the treatment of iCCA. PATIENTS AND METHODS: We retrospectively analyzed the cases of 156 patients diagnosed with iCCA between 1990 and 2014 in our center. Patients were divided into subgroups depending on the presence and severity of liver cirrhosis and the type of treatment. Clinical data, patient characteristics, and overall survival were compared between these groups. RESULTS: Forty-seven (30%) of 156 patients had liver cirrhosis, predominantly with Child-Pugh scores A (n=27) and B (n=12). The median survival differed between patients receiving tumor resection (34 months), chemotherapy (10 months), and best supportive care (2 months). An Eastern Cooperative Oncology Group Performance Status score more than 1 was a predictor of poor survival in all patients (P<0.001), independent of the presence of cirrhosis. Resection could be performed less frequently in cirrhotic patients (6 vs. 31 patients; P=0.04). If resection was performed, the presence of cirrhosis A/B did not influence survival. Cirrhosis A/B did not influence the outcome in patients receiving chemotherapy either. In cirrhotic patients receiving chemotherapy, cancer antigen 19-9 levels above 129 U/ml were associated with a significantly shorter survival (22.5 vs. 3 months, P=0.0003). CONCLUSION: The presence of liver cirrhosis in iCCA has been underestimated. There was no difference in survival between noncirrhotic patients and patients with compensated cirrhosis. Patients' general condition seems to be of more prognostic value in the treatment of iCCA than the presence of cirrhosis. Therefore, the presence of cirrhosis A/B should not prevent patients with a good Eastern Cooperative Oncology Group Performance Status score from receiving tumor resection or chemotherapy.
EVALuna2:34071

Endoscopic recanalization of complete esophageal obstruction - Vitali, Francesco; Naegel, Andreas; Pfeifer, Lukas; Goetz, Martin; Neurath, Markus; Rath, Timo; Siebler, Jürgen (Surgical Endoscopy, 2021)
Background and aims Complete esophageal obstruction (CEO) is a rare complication after radiochemotherapy that dramatically impairs quality of life. Within this study, we assessed the outcome of two different endoscopic techniques for lumen restoration in patients with CEO.
CRIS-Team WoS Importer:2021-02-26

How Much Liver Tissue Is Required for Sufficient Histological Staging in Patients with Primary Biliary Cholangitis? - Vetter, Marcel; Kremer, Andreas; Agaimy, Abbas; Pfeifer, Lukas; Neurath, Markus; Zopf, Steffen; Siebler, Jürgen (Digestion, 2020)
Introduction: Histological alterations in primary biliary cholangitis (PBC) are heterogeneously distributed throughout the liver. Thus, the quality of histological staging is probably dependent on the available amount of liver tissue. The goals of this study were to test this hypothesis and to define biopsy conditions for obtaining sufficient tissue. Methods: In this retrospective analysis, we investigated 34 patient cases who fulfilled the criteria of the European Association for the Study of the Liver (EASL) for PBC and underwent a mini-laparoscopic liver biopsy between 2011 and 2018 using 16 or 18G needles. For histological assessment of fibrosis, we used the Ishak score, and the amount of tissue was measured by the number of portal fields. Histological staging was compared with the macroscopic mini-laparoscopic fibrosis score (MLFS), and non-invasive liver stiffness measurements using acoustic radiation force impulse (ARFI) imaging and the FIB-4 score. Results: Biopsy was successful in 33 of 34 patients (97%). Fibrosis assessment by MLFS and ARFI correlated strongly with each other (r = 0.7088, p = 0.000017). However, the correlation of both methods with the histological staging was weaker (MLFS vs. histology: r = 0.4231, p = 0.0142; ARFI vs. histology: r = 0.3564, p = 0.0577). The correlation of ARFI and MLFS with the histological staging was better in the subgroup of biopsies with at least 10 portal fields (= SG≥10PF) (MLFS vs. histology: r = 0.6369, p = 0.006; ARFI vs. histology: r = 0.7538, p = 0.0012). FIB-4 correlated weakly with the histological staging, which was statistically not significant (all samples: r = 0.2693, p = 0.1296; SG≥10PF: r = 0.2244, p = 0.3866). The number of portal fields correlated well with the length of the samples (r = 0.6436, p = 0.00012). The probability to attain at least 10 portal fields depended on the needle diameter and number of samples (1 × 16G or 18G [n = 10]: 30.0%; 2 × 18G [n = 15]: 53.3%; 2 × 16G [n = 5]: 100%; p = 0.0414). Conclusion: ARFI and MLFS are probably well suited for the assessment of liver fibrosis in patients with PBC. A minimum of 10 portal fields could improve the histological assessment in PBC and can probably be achieved by obtaining two 16G biopsies.
CRIS-Team Scopus Importer:2020-06-19

Improvement of clinical management and outcome in hepatocellular carcinoma nowadays compared with historical cohorts - Schellhaas, Barbara; Strobel, Deike; Stumpf, Miriam; Ganslmayer, Marion; Pfeifer, Lukas; Görtz, Rüdiger; Neurath, Markus; Zopf, Steffen (European Journal of Gastroenterology & Hepatology, 2018)
OBJECTIVES: Therapeutic approaches in the treatment of hepatocellular carcinoma (HCC) depend on tumour stage, liver function and patient comorbidities. The aim of this study was to investigate the influence of tumour stage and therapeutic approach on overall survival in HCC. MATERIALS AND METHODS: Two hundred and fourteen patients with HCC diagnosed between December 2012 and May 2017 were assessed retrospectively for tumour stage [Barcelona Clinic Liver Cancer (BCLC)], liver function (Child-Pugh score), therapeutic approach and outcome (mean survival time). The results were compared to two historical cohorts from our centre diagnosed between 1999 and 2013 and 1988 and 1999, respectively. RESULTS: Nowadays, HCC is diagnosed in earlier tumour stages and with better liver function compared with the historical cohorts (P<0.001). Survival times depend on both BCLC stages and liver function for all therapeutic approaches. The 1-year survival rate in the present cohort was 79.4% compared with 58.6% in the historical cohort.In terms of BCLC stages, therapeutic approaches followed HCC guidelines in 43.9% of cases.Whereas the percentage of patients receiving resection or ablation did not change between the historical and the present cohort, there was a tendency towards a decrease in transarterial chemoembolization, with a shift towards selective internal radiotherapy, accompanied by an increase in systemic therapy with sorafenib.Also, the percentage of patients receiving single instead of multiple therapies was significantly higher in the present cohort compared with the historical cohort (P=0.016). In 62/83 patients receiving single therapy (64.7%), tumour remission was maintained during the period of follow-up. CONCLUSION: HCC is increasingly being diagnosed in earlier stages, so that single therapy is often sufficient. Besides BCLC stages, therapy in HCC must consider liver function, tumour location, local expertise and patients' comorbidities and preferences. Further research is needed to evaluate the benefit of early multimodal concepts. Therapeutic approaches in HCC remain individual decisions.
EVALuna2:35130

Interobserver Agreement for Contrast-Enhanced Ultrasound (CEUS)-Based Standardized Algorithms for the Diagnosis of Hepatocellular Carcinoma in High-Risk Patients - Schellhaas, Barbara; Pfeifer, Lukas; Kielisch, Christian; Görtz, Rüdiger; Neurath, Markus; Strobel, Deike (Ultraschall in der Medizin, 2018)
OBJECTIVES: This pilot study aimed at assessing interobserver agreement with two contrast-enhanced ultrasound (CEUS) algorithms for the diagnosis of hepatocellular carcinoma (HCC) in high-risk patients. METHODS: Focal liver lesions in 55 high-risk patients were assessed independently by three blinded observers with two standardized CEUS algorithms: ESCULAP (Erlanger Synopsis of Contrast-Enhanced Ultrasound for Liver Lesion Assessment in Patients at risk) and ACR-CEUS-LI-RADSv.2016 (American College of Radiology CEUS-Liver Imaging Reporting and Data System). Lesions were categorized according to size and ultrasound contrast enhancement in the arterial, portal-venous and late phase. Interobserver agreement for assessment of enhancement pattern and categorization was compared between both CEUS algorithms. Additionally, diagnostic accuracy for the definitive diagnosis of HCC was compared. Histology and/or CE-MRI and follow-up served as reference standards. RESULTS: 55 patients were included in the study (male/female, 44/ 11; mean age: 65.9 years). 90.9 % had cirrhosis. Histological findings were available in 39/55 lesions (70.9 %). Reference standard of the 55 lesions revealed 48 HCCs, 2 intrahepatic cholangiocellular carcinomas (ICCs), and 5 non-HCC-non-ICC lesions. Interobserver agreement was moderate to substantial for arterial phase hyperenhancement (ĸ = 0.53 - 0.67), and fair to moderate for contrast washout in the portal-venous or late phase (ĸ = 0.33 - 0.53). Concerning the CEUS-based algorithms, the interreader agreement was substantial for the ESCULAP category (ĸ = 0.64 - 0.68) and fair for the CEUS-LI-RADS® category (ĸ = 0.3 - 0.39). Disagreement between observers was mostly due to different perception of washout. CONCLUSION: Interobserver agreement is better for ESCULAP than for CEUS-LI-RADS®. This is mostly due to the fact that perception of contrast washout varies between different observers. However, interobserver agreement is good for arterial phase hyperenhancement, which is the key diagnostic feature for the diagnosis of HCC with CEUS in the cirrhotic liver.
EVALuna2:35127

Interobserver and intermodality agreement of standardized algorithms for non-invasive diagnosis of hepatocellular carcinoma in high-risk patients: CEUS-LI-RADS versus MRI-LI-RADS - Schellhaas, Barbara; Hammon, Matthias; Strobel, Deike; Pfeifer, Lukas; Kielisch, Christian; Görtz, Rüdiger; Janka, Rolf Matthias; Neurath, Markus; Uder, Michael; Seuß, Hannes; Cavallaro, Alexander Josef (European Radiology, 2018)
OBJECTIVES: We compared the interobserver agreement for the recently introduced contrast-enhanced ultrasound (CEUS)-based algorithm CEUS-LI-RADS (Liver Imaging Reporting and Data System) versus the well-established magnetic resonance imaging (MRI)-LI-RADS for non-invasive diagnosis of hepatocellular carcinoma (HCC) in high-risk patients. METHODS: Focal liver lesions in 50 high-risk patients (mean age 66.2 ± 11.8 years; 39 male) were assessed retrospectively with CEUS and MRI. Two independent observers reviewed CEUS and MRI examinations, separately, classifying observations according to CEUS-LI-RADSv.2016 and MRI-LI-RADSv.2014. Interobserver agreement was assessed with Cohen's kappa. RESULTS: Forty-three lesions were HCCs; two were intrahepatic cholangiocarcinomas; five were benign lesions. Arterial phase hyperenhancement was perceived less frequently with CEUS than with MRI (37/50 / 38/50 lesions = 74%/78% [CEUS; observer 1/observer 2] versus 46/50 / 44/50 lesions = 92%/88% [MRI; observer 1/observer 2]). Washout appearance was observed in 34/50 / 20/50 lesions = 68%/40% with CEUS and 31/50 / 31/50 lesions = 62%/62%) with MRI. Interobserver agreement was moderate for arterial hyperenhancement (ĸ = 0.511/0.565 [CEUS/MRI]) and "washout" (ĸ = 0.490/0.582 [CEUS/MRI]), fair for CEUS-LI-RADS category (ĸ = 0.309) and substantial for MRI-LI-RADS category (ĸ = 0.609). Intermodality agreement was fair for arterial hyperenhancement (ĸ = 0.329), slight to fair for "washout" (ĸ = 0.202) and LI-RADS category (ĸ = 0.218) CONCLUSION: Interobserver agreement is substantial for MRI-LI-RADS and only fair for CEUS-LI-RADS. This is mostly because interobserver agreement in the perception of washout appearance is better in MRI than in CEUS. Further refinement of the LI-RADS algorithms and increasing education and practice may be necessary to improve the concordance between CEUS and MRI for the final LI-RADS categorization. KEY POINTS: • CEUS-LI-RADS and MRI-LIRADS enable standardized non-invasive diagnosis of HCC in high-risk patients. • With CEUS, interobserver agreement is better for arterial hyperenhancement than for "washout". • Interobserver agreement for major features is moderate for both CEUS and MRI. • Interobserver agreement for LI-RADS category is substantial for MRI, and fair for CEUS. • Interobserver-agreement for CEUS-LI-RADS will presumably improve with ongoing use of the algorithm.
EVALuna2:34689

I-scan optical enhancement for the in vivo prediction of diminutive colorectal polyp histology: Results from a prospective three-phased multicentre trial - Klenske, Entcho; Zopf, Steffen; Neufert, Clemens; Naegel, Andreas; Gschossmann, Juergen; Muehldorfer, Steffen; Pfeifer, Lukas; Fischer, Sören; Vitali, Francesco; Iacucci, Marietta; Ghosh, Subrata; Rath, Michelle G.; et al. (PLoS ONE, 2018)
BACKGROUND AND AIMS: Dye-less chromoendoscopy is an emerging technology for colorectal polyp characterization. Herein, we investigated whether the newly introduced I-scan optical enhancement (OE) can accurately predict polyp histology in vivo in real-time. METHODS: In this prospective three-phased study, 84 patients with 230 diminutive colorectal polyps were included. During the first two study phases, five endoscopists assessed whether analysis of polyp colour, surface and vascular pattern under i-scan OE can differentiate in vivo between adenomatous and hyperplastic polyps. Finally, junior and experienced endoscopists (JE, EE, each n = 4) not involved in the prior study phases made a post hoc diagnosis of polyp histology using a static i-scan OE image database. Histopathology was used as a gold-standard in all study phases. RESULTS: The overall accuracy of i-scan OE for histology prediction was 90% with a sensitivity, specificity, positive (PPV) and negative prediction value (NPV) of 91%, 90%, 86% and 94%, respectively. In high confidence predictions, the diagnostic accuracy increased to 93% with sensitivity, specificity, PPV and NPV of 94%, 91%, 89% and 96%. Colonoscopy surveillance intervals were predicted correctly in ≥ 90% of patients. In the post hoc analysis EE predicted polyp histology under i-scan OE with an overall accuracy of 91%. After a single training session, JE achieved a comparable diagnostic performance for predicting polyp histology with i-scan OE. CONCLUSION: The histology of diminutive colorectal polyps can be accurately predicted with i-scan OE in vivo in real-time. Furthermore, polyp differentiation with i-scan OE appears to require only a short learning curve.
EVALuna2:35169

LI-RADS-CEUS - Proposal for a Contrast-Enhanced Ultrasound Algorithm for the Diagnosis of Hepatocellular Carcinoma in High-Risk Populations - Schellhaas, B.; Wildner, Dane; Pfeifer, Lukas; Görtz, Rüdiger; Hagel, Alexander; Neurath, Markus; Strobel, Deike (Ultraschall in der Medizin, 2016)
Purpose: To develop a contrast-enhanced ultrasound algorithm (LI-RADS-CEUS = liver imaging reporting and data system with contrast-enhanced ultrasound) for the diagnosis of hepatocellular carcinoma (HCC) in patients at risk. Materials and Methods: A CEUS algorithm (LI-RADS-CEUS) was designed analogously to CT- and MRI-based LI-RADS. LI-RADS-CEUS was evaluated retrospectively in 50 patients at risk with confirmed HCC or non-HCC lesions (test group) with subsequent validation in a prospective cohort of 50 patients (validation group). Results were compared to histology, CE-CT and CE-MRI as reference standards. Results: Tumor diagnosis in the test group/validation group (n = 50/50) were 46/41 HCCs, 3/3 intrahepatic cholangiocellular carcinomas (ICCs) and 1/6 benign lesions. The diagnostic accuracy of LI-RADS-CEUS for HCC, ICC and non-HCC-non-ICC-lesions was 89 %. For the diagnosis of HCC, the diagnostic accuracy was 93.5 % (43/46 cases) in the test group and 95.1 % (39/41 cases) in the validation group. The sensitivity, specificity, positive predictive value (PPV) and negative predictive value (NPV) were 94.3 %, 66.6 %, 94.3 % and 66.6 %, respectively (mean values from both cohorts). Histological findings of HCC were available in 40 versus 23 cases (in total: G1 / G2/G3: 15/35/13). Arterial hyperenhancement was seen in 68/87 (78.2 %) of HCCs. Arterial hyperenhancement with subsequent portal venous or late phase hypoenhancement was seen in 66 % of HCCs. Conclusion: LI-RADS-CEUS offers a CEUS algorithm for standardized assessment and reporting of focal liver lesions in patients at risk for HCC. Arterial hyperenhancement in CEUS is the key feature for the diagnosis of HCC in patients at risk, whereas washout is not a necessary prerequisite.
EVALuna2:2223

Liver stiffness assessed by acoustic radiation force impulse (ARFI) technology is considerably increased in patients with cholestasis - Pfeifer, Lukas; Strobel, Deike; Neurath, Markus; Wildner, D. (Ultraschall in der Medizin, 2014)
To explore the impact of cholestasis on liver stiffness assessed by acoustic radiation force impulse (ARFI) technology.Over a period of four months, patients with sonographic cholestasis and increased cholestatic blood values (Bilirubin, ?GT, AP > 2 times ULN) scheduled for endoscopic therapy were recruited. Exclusion criteria were: known liver disease; signs of cirrhosis at ultrasound (irregular liver veins and/or surface); heart insufficiency (NYHA III-VI). ARFI (Siemens S2000), ultrasound and blood examinations were performed before and in a subgroup after successful biliary drainage.In total, 21 patients with cholestasis were included in the study. ARFI measurements were above the cut-off for cirrhosis (1.8 m/s) in all patients with a mean of 2.91 m/s ± 0.89 m/s without a history or signs of cirrhosis. Bilirubin, ?GT and AP were elevated on average to 9.7 ± 5.3 mg/dl, 1192 ± 960 U/l and 730 ± 389 U/l. A subgroup of 10 patients was measured after successful drainage. ARFI measurements declined in all patients of that subgroup on average by 0.76 m/s at a mean time interval of 4.5 days (p < 0.001).Cholestasis significantly increases liver stiffness assessed by ARFI. Therefore, it is important to exclude profound cholestasis when using ARFI for evaluating patients for liver fibrosis.
EVALuna2:1875

Multispectral Optoacoustic Tomography for Assessment of Crohn's Disease Activity - Knieling, Ferdinand; Neufert, Clemens; Hartmann, Arndt; Claussen, Jing; Urich, Alexander; Egger, Cornelia; Vetter, Marcel; Fischer, Sarah; Pfeifer, Lukas; Hagel, Alexander; Kielisch, Christian; Görtz, Rüdiger; et al. (New England Journal of Medicine, 2017)
EVALuna2:33821

Multispectral Optoacoustic Tomography in Crohn's Disease: Noninvasive Imaging of Disease Activity - Waldner, Maximilian; Knieling, Ferdinand; Egger, Cornelia; Morscher, Stefan; Claussen, Jing; Vetter, Marcel; Kielisch, Christian; Fischer, Sören; Pfeifer, Lukas; Hagel, Alexander; Görtz, Rüdiger; Wildner, Dane; et al. (Gastroenterology, 2016)
EVALuna2:2071

Prospective Evaluation of Acoustic Radiation Force Impulse (ARFI) Elastography and High-Frequency B-Mode Ultrasound in Compensated Patients for the Diagnosis of Liver Fibrosis/Cirrhosis in Comparison to Mini-Laparoscopic Biopsy - Pfeifer, Lukas; Zopf, Steffen; Schwitulla, Judith; Wildner, Dane; Wachter, David; Neurath, Markus; Strobel, Deike; Siebler, Jürgen (Ultraschall in der Medizin, 2015)
Purpose: Ultrasound is a well-established noninvasive test for assessing patients with liver disease. This study aims to prospectively compare ultrasound to the new technique elastography (ARFI) for the assessment of liver fibrosis/cirrhosis. Materials and Methods: High-frequency B-mode ultrasound (liver surface/vein irregularity, liver homogeneity, spleen size), ARFI quantification, mini-laparoscopic liver evaluation including biopsy were prospectively obtained in compensated patients scheduled for liver biopsy. For the diagnosis of cirrhosis, a combined gold standard (cirrhosis at histology and/or at macroscopic liver evaluation) was used. Results: Out of 157 patients, 35 patients were diagnosed cirrhotic. Ultrasound (combination of liver vein and/or surface irregularity) showed no significant difference compared to ARFI quantification for the diagnosis of significant liver fibrosis (Ishak> = 3) and cirrhosis. Diagnosis of cirrhosis had a sensitivity/specificity/PPV/NPV of 83 %(± 12) / 82 %(± 7) / 57 %(± 14) / 94 %(± 4), respectively, with ultrasound and 86 %(± 12) / 81 %(± 7) / 57 %(± 13) / 95 %(± 4), respectively, with ARFI quantification. The sensitivity/specificity/PPV/NPV for the detection of significant fibrosis were 68 %(± 13) / 86 %(± 7) / 71 %(± 13) / 84 %(± 7), respectively, for ultrasound and 70 %(± 12) / 84 %(± 7) / 69 %(± 12) / 84 %(± 7), respectively, for ARFI quantification. Conclusion: ARFI elastography and high-frequency B-mode ultrasound show similar and good results for the diagnosis of compensated liver cirrhosis and high-grade fibrosis. A key benefit of both methods is the high NPV suggesting them as noninvasive exclusion tests.
EVALuna2:2049

Quantitative perfusion analysis in pancreatic contrast enhanced ultrasound (DCE-US): a promising tool for the differentiation between autoimmune pancreatitis and pancreatic cancer - Vitali, Francesco; Pfeifer, Lukas; Janson, C.; Görtz, Rüdiger; Neurath, Markus; Strobel, Deike; Wildner, Dane (Zeitschrift für Gastroenterologie, 2015)
In the work-up of focal pancreatic lesions autoimmune pancreatitis (AIP) is a rare differential diagnosis to pancreatic cancer (PC) with similar clinical constellations. The aim of our study was to compare differences between proven AIP and PC using transabdominal dynamic contrast enhanced ultrasound (DCE-US). Therefore we recorded 3-minute-clips of CEUS examinations and analyzed perfusion parameters with VueBox(®)-quantification software. To obtain DCE-US Parameters, Regions-of-Interest were selected within the lesions and the surrounding pancreas parenchyma, serving as reference tissue. We compared 3 patients with AIP (mean age: 58 years; lesion mean size: 40 mm) to 17 patients with PC (mean age: 68 years; lesion mean size: 35.9 mm). Significant differences between PC and parenchyma could be found in the following parameters: Peak-Enhancement (PE), Wash-in-and-Wash-out-AUC, Wash-in Perfusion-Index. PE of AIP was comparable to normal parenchyma. The relation of PE between parenchyma and lesion (?PE) AIP and PC was significantly different [AIP: 0.21 (± 0.06); PC: 0.81 (± 0.1); p < 0.01]. PE of neoplastic lesions was significantly lower as AIP and normal parenchyma (p < 0.01). Therefore perfusion analysis in DCE-US can help to differentiate hypovascular PC from AIP presenting nearly isovascular time intensity curves. Diagnostic accuracy of DCE-US in this setting has to be validated in future prospective studies in comparison to CT and MRI.
EVALuna2:1985

Retrograde inspection vs standard forward view for the detection of colorectal adenomas during colonoscopy: A back-to-back randomized clinical trial - Rath, Timo; Pfeifer, Lukas; Neufert, Clemens; Kremer, Andreas; Leppkes, Moritz; Hoffman, Arthur; Neurath, Markus; Zopf, Steffen (World Journal of Gastroenterology, 2020)
BACKGROUND: The adenoma detection rate (ADR) is inversely associated with the incidence of interval colorectal cancer and serves as a benchmark quality criterion during screening colonoscopy. However, adenoma miss rates reach up to 26% and studies have shown that a second inspection of the right colon in retroflected view (RFV) can increase ADR. AIM: To assess whether inspection of the whole colon in RFV compared to standard forward view (SFV) can increase ADR. METHODS: Patients presenting for screening or surveillance colonoscopy were invited to participate in this randomized controlled trial and randomized into two arms. In RFV arm colonoscopy was initially performed with SFV, followed by a second inspection of the whole colon in RFV. In the SFV arm first withdrawal was performed with SFV, followed by a second inspection of the whole colon again with SFV. Number, size and morphology of polyps found during first and second inspection in each colonic segment were recorded and all polyps were removed and sent for histopathology in separate containers. RESULTS: Two hundred and five patients were randomly assigned to the RFV (n = 101) and SFV (n = 104) arm. In the RFV arm, both polyp detection rate (PDR) and ADR were increased under second inspection in RFV (PDR 1st SFV: 39.8%, PDR 2nd RFV: 46.6%; ADR 1st SFV: 35.2%, ADR 2nd RFV: 42%). Likewise, in the SFV arm, PDR and ADR were increased under second inspection (PDR 1st SFV: 37.5%, PDR 2nd SFV: 46.6%; ADR 1st SFV: 34.1%, ADR 2nd SFV: 44.3%) with no significant differences in ADR and PDR between the SFV and RFV arm. Mean number of adenomas per patient (APP) was increased in the RFV and SFV (APP RFV arm: 1st SFV: 1.71; 2nd RFV: 2.38; APP SFV arm: 1st SFV: 1.83, 2nd SFV:2.2). The majority of adenomas additionally found during second inspection in RFV or in SFV were located in the transverse and left-sided colon and were > 5 mm in size. CONCLUSION: Second inspection of the whole colon leads to increased adenoma detection with no differences between SFV and RFV. Hence, increased detection is most likely a feature of the second inspection itself but not of the inspection mode.
CRIS-Team Scopus Importer:2020-05-22
Keywords: Adenoma; Adenoma detection rate; Colonoscopy; Colorectal cancer

Shear Wave Dispersion Imaging for the Characterization of Focal Liver Lesions - A Pilot study - Jesper, Daniel; Fiedler, Steffen; Klett, Daniel; Waldner, Maximilian; Schellhaas, Barbara; Zundler, Sebastian; Neurath, Markus; Pfeifer, Lukas (Ultraschall in der Medizin, 2021)
Purpose Shear wave dispersion imaging is a novel ultrasound-based technique, which analyzes the speed of different shear wave components depending on their frequency. The dispersion of shear wave speed correlates with the viscosity of the liver parenchyma. The aim of this prospective study was to evaluate the use of shear wave dispersion imaging in focal liver lesions in the non-cirrhotic liver. Methods Patients with unclear focal liver lesions in B-mode ultrasound were prospectively assigned to shear wave dispersion imaging (m/s/kHz). Measurements were conducted within the lesion and in the liver parenchyma of the right liver lobe using an intercostal window. Histology and contrast-enhanced ultrasound served as the reference for the characterization of the lesions. Results Out of 46 patients included in this study, 24 had liver metastases and 22 had benign liver lesions. Benign lesions consisted mostly of hemangiomas (n=12) and focal nodular hyperplasia (n=8). Malignant lesions showed significantly lower shear wave dispersion (13.0±2.45 m/s/kHz) compared to benign tumors (15.2±2.74 m/s/kHz, p<0.01). In further subgroup analysis, the difference was significant for hemangiomas (15.32±2.42 m/s/kHz, p=0.04) but not for FNHs (14.98±3.36 m/s/kHz, p=0.38). The dispersion of reference liver parenchyma did not differ significantly between the groups (p=0.54). Conclusion The quantification of viscosity by shear wave dispersion is a new parameter for the characterization of focal liver lesions with higher dispersion values in hemangiomas and lower dispersion values in metastases. However, it cannot differentiate reliably between benign and malignant lesions.
CRIS-Team Scopus Importer:2021-10-29
Keywords: focal liver lesion; shear wave dispersion; shear wave elastography; ultrasound

The importance of pancreatic inflammation in endosonographic diagnostics of solid pancreatic masses - Vitali, Francesco; Strobel, Deike; Frulloni, Luca; Heinrich, Marc Christopher; Pfeifer, Lukas; Görtz, Rüdiger; Hundorfean, Gheorghe; Wachter, David Lukas; Wachter, David; Grützmann, Robert; Bernatik, Thomas; Neurath, Markus; et al. (Medical Ultrasonography, 2018)
AIMS: Endosonography (EUS) is one of the main diagnostic tools for the differential diagnosis of pancreatic masses. The aim of our study was to describe the value of this technique in the work-up of solid pancreatic lesions, considering the influence of the morphological evidence of pancreatic inflammation in the diagnostic process. MATERIAL AND METHODS: Retrospective analysis of prospectively collected data in our tertiary University center. From March 2007 to October 2015, 218 patients underwent EUS for a suspected solid pancreatic neoplasm (based on previous cross-sectional imaging results, idiopatic acute pancreatitis, weight loss, pancreatic hyperenzymemia, painless jaundice or elevated Ca 19-9 values). RESULTS: Malignant lesions were diagnosed in 98 (45%) patients. Sensitivity of EUS for malignancy was 91% and specificity 89.2%. Signs of pancreatic inflammation in the surrounding pancreatic parenchyma around the focal lesion were present in 97 patients (44.4%)(more often in men, smokers and drinkers, and the most common etiology was focal chronic pancreatitis) and in these patients the sensitivity and sensibility dropped to 44% and 87.1%, respectively. In patients without signs of pancreatic inflammation, the pancreatic focal lesions were adenocarcinoma, neuroendocrine tumor, ventral/dorsal split, non-pancreatic pathology, pancreatic lipomatosis and autoimmune pancreatitis. CONCLUSION: Pancreatic inflammation (either focal or involving the whole gland) lowers the diagnostic sensibility of EUS in the work- up of pancreatic masses suspected for cancer, requiring further invasive diagnostic methods. Focal autoimmune pancreatitis and paraduodenal pancreatitis are still confused with pancreatic cancer, even in the absence of pancreatic inflammation.
EVALuna2:35194

Transabdominal ultrasonography for confirmation of accurate percutaneous endoscopic gastrostomy tube placement: analysis of patient- and procedure-related complications - Wildner, Dane; Pfeifer, Lukas; Vitali, Francesco; Neurath, Markus; Albrecht, Heinz (Medical Ultrasonography, 2022)
Aims: Technique-related factors, patient-related factors, and localization determine the risk for complications in percutaneous endoscopic gastrostomy (PEG) tube placement. The objective of this study was to identify patient characteristics and ultrasonographic parameters after PEG tube placement concerning localization, which correlate with complications. Material and methods: Patients undergoing PEG-tube placement were examined by abdominal ultrasound after dismissal from the endoscopic recovery room. Patient demographics, PEG characteristics, ultrasonographic parameters and complications were retrospectively analyzed. Results: Of 64 enrolled patients, 59.4% were male and the mean age was 62.3 years. A significant negative correlation between complications at PEG placement and Body-Mass-Index (BMI; kg/m(2)) was observed (Spearman's Rho: -0.382; p=0.002). A low BMI <18 tended to be more frequent in the group with complication-related PEG removal compared to patients without (18.2% vs. 1.9%). Further descriptive analysis revealed that 4 patients (36.4% of N=11) with and 5 patients (9.4% of N=53) without PEG removal due to complications already had complications at the time of PEG placement. Of the patients with complications during follow-up, those with a peritoneal course (N=10) in ultrasound tended to have a lower BMI (mean +/- standard deviation: 22.5 +/- 6.5 vs. 26.8 +/- 5.9) compared to those without (N=5). In all 4 patients with a triad of follow-up complications, peritoneal course, and complications at PEG placement, the tube was removed due to complications. Conclusions: Post-PEG-placement ultrasonography can help to determine complications in specific procedure-related conditions. A low BMI was found to be a relevant predictor of PEG-related complications, substantiating the need for early intervention in potentially PEG-relevant indications.
CRIS-Team WoS Importer:2023-03-03

Two-dimensional shear-wave elastography: a new method comparable to acoustic radiation force impulse imaging? - Schellhaas, Barbara; Strobel, Deike; Wildner, Dane; Görtz, Rüdiger; Neurath, Markus; Pfeifer, Lukas (European Journal of Gastroenterology & Hepatology, 2017)
OBJECTIVES: Two-dimensional shear-wave elastography (2D-SWE) is an ultrasound-based technique for the noninvasive assessment of tissue stiffness. In contrast to the well-established point-shear-wave elastography (pSWE) method acoustic radiation force impulse imaging, there is little evidence on the performance and usefulness of 2D-SWE in the assessment of liver stiffness. Thus, the aim of our study was to compare 2D-SWE versus pSWE. MATERIALS AND METHODS: 2D-SWE and pSWE were performed in 20 cirrhotic patients, 20 healthy individuals and an elasticity phantom. Stiffness values, examination time and number of measurements were compared. For 2D-SWE, the influence of size of the region of interest (ROI) was assessed. RESULTS: Elastography values in healthy individuals were slightly higher for 2D-SWE versus pSWE (1.4 m/s, range: 1.21-1.68 vs. 1.23 m/s, range: 1.07-1.39). In cirrhotic patients, there were no significant differences (3.06 m/s, range: 1.83-5.35 vs. 3 m/s, range: 1.67-4.37 m/s). Examination times were significantly longer for 2D-SWE in both patient groups (mean values for healthy/cirrhotic patients: 129.6/157.1 vs. 75/71.6 s). For 2D-SWE, variation of ROI size (5, 10, 20 mm) produced comparable results. After eight measurements, 90% of cirrhotic patients showed less than 5% of deviation from the results after the gold standard of 10 measurements; for healthy individuals, this was observed after six measurements. CONCLUSION: 2D-SWE seems to be comparable to pSWE (acoustic radiation force impulse-imaging) in cirrhotic patients, with slightly higher values in healthy individuals. 2D-SWE measurements require considerably more time. For 2D-SWE, ROI size seems to be of minor importance; multiple measurements should be obtained as single measurements differ. These preliminary results should be confirmed in larger patient collectives with histology as the reference standard.
EVALuna2:33813

Ultrasound-Based Attenuation Imaging for the Non-Invasive Quantification of Liver Fat-A Pilot Study on Feasibility and Inter-Observer Variability - Jesper, Daniel; Klett, Daniel; Schellhaas, Barbara; Pfeifer, Lukas; Leppkes, Moritz; Waldner, Maximilian; Neurath, Markus; Strobel, Deike (IEEE Journal of Translational Engineering in Health and Medicine, 2020)
Attenuation imaging is a novel, ultrasound-based technique to objectively detect and quantify liver steatosis. In this study, we evaluated the performance and inter-observer variability of attenuation imaging and compared it to a known quantification method of liver fat, the hepatorenal index (HRI). Two observers measured attenuation coefficients (AC) in an attenuation phantom, 20 healthy volunteers and 27 patients scheduled for biopsy for suspected diffuse liver disease. Results were compared with the HRI and histological findings. Both observers were blinded to the results of the biopsy and the measurements of the other observer. Our results showed that patients with moderate (S2, 33-66%) and severe fatty infiltration of the liver (S3, >66%) showed significantly higher ACs in comparison to patients with a liver fat fraction of less than 33% (S0/1). There was no significant difference in AC-values of patients with fatty infiltration of less than 5% (S0) and 5-32% (S1). In the Receiver Operating Characteristic (ROC)-analysis, the area under the curve (AUC)-values for the detection of moderate and severe steatosis were excellent at 0.98. Cut-off values were 0.64 dB/cm/MHz for the detection of S2- A nd 0.68 dB/cm/MHz for the detection of S3-steatosis. The inter-observer agreement of attenuation imaging was very good with an intraclass correlation coefficient (ICC) of 0.92 in patient and 0.96 in phantom measurements. The ICC decreased with depth in the phantom measurements. In summary, attenuation imaging showed very good inter-observer agreement and is a promising tool for the detection and quantification of moderate and severe hepatic steatosis.
CRIS-Team Scopus Importer:2020-07-31
Keywords: Attenuation imaging; fatty liver; hepatic fat; hepatic steatosis; hepatorenal index; inter-observer; liver steatosis; NAFLD; NASH; ultrasound